Hubungan Ekspresi Vascular Endothelial Growth Factor (VEGF) dengan Derajat Diferensiasi dan Invasi Limfovaskular pada Adenokarsinoma Kolorektal - Nana Liana; Noza Hilbertina; Loli Devianti; Husna Yetti (Majalah Patologi Indonesia, 2022)
BackgroundColorectal carcinoma is the third most common malignancy in the world. Colorectal carcinoma is a heterogeneous tumor withdifferent clinical pathologic features and prognostic values. For the same tumor-stage, patients could have difference prognosis andit has been suggested that the angiogenesis might be correlated with the prognosis, especially expression of vascular endothelialgrowth factor (VEGF) as the main pro-angiogenic factor. High VEGF expression in colorectal adenocarcinoma is associated withincreased blood vessels in invasive tumor area, cell proliferation and metastases. However, relation VEGF expression with thedegree of differentiation and lymphovascular invasion is not known.MethodsThis was a retrospective observational study with cross sectional approach. Samples were obtained from 39 paraffin blocks withdiagnosis adenocarcinoma not otherwise specific (NOS) in four Anatomical Pathology Laboratory in West Sumatera 2018 andevaluated for degree of differentiation and lymphovascular invasion. VEGF expressions in tumor cell were analyzed usingimmunohistochemistry staining. Bivariate statistical analysis used Fisher's Exact test and value p<0.05 was considered significant.ResultsColorectal adenocarcinoma with high grade differentiation entirely had high VEGF expression (100%), while low gradedifferantiation with high VEGF expression was 60.7%. Lymphovascular invasion positive was mostly found with high VEGFexpression (80.6%). Statistical analysis showed significant association between VEGF expression with degree of differentiation(p=0.017) and lymphovascular invasion (p=0.028).ConclusionThe conclusion was VEGF expression had significant association with degree of differentiation and lymphovascular invasion ofcolorectal adenocarcinoma.